Ground-Based and Airborne Instrumentation for Astronomy IX 2022
DOI: 10.1117/12.2629996
|View full text |Cite
|
Sign up to set email alerts
|

Astrophotonic solutions for spectral cross-correlation techniques

Abstract: Using photonic devices, we developed a new approach to traditional spectroscopy where the spectral crosscorrelation with a template spectrum can be done entirely on-device. By creating photonic devices with a carefully designed, modulated transmission spectrum, the cross-correlation can be carried out optically without requiring any dispersion, vastly simplifying the instrument and reducing its cost. The measured correlation lag can be used for detecting atomic/molecular species within and determining the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As the filter is scanned through wavelength, its varying overlap with spectral features from the molecular structure means that the transmitted intensity will be modulated. Using the model presented by Sivanandam et al 11 the transmitted intensity for a given spectral feature can be expressed as:…”
Section: Cross-correlation Spectroscopy: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…As the filter is scanned through wavelength, its varying overlap with spectral features from the molecular structure means that the transmitted intensity will be modulated. Using the model presented by Sivanandam et al 11 the transmitted intensity for a given spectral feature can be expressed as:…”
Section: Cross-correlation Spectroscopy: Theorymentioning
confidence: 99%
“…A system employing a notch filter has been modeled by Cheriton et al 9 , who demonstrated recovery of the IR spectrum of Venus. Various groups have independently pursued architectures to deliver improved sensors based on the ability of FBGs to create complex wavelength-selective filters, including the work of Tuthill 10 and Sivanadam et al 11 , however prior to the present paper, a major challenge has been in the fabrication of the required bespoke tailored FBG to exactly match spectral response of the target molecule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations